Vision based control algorithms for a small size robot soccer team - Karaoğuz, Hakan. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
Multi-robot coordination is one of the hot topics of today's robotics research. In our case, our main concern is to build up a small sized (SSL) robot soccer team. Robot soccer requires e ective and fast robot control and coordination in order to score goals while avoiding frequent collisions with opponent robots. In this thesis, our multi-robot platform and current control techniques we use are discussed. Our robots have 4 wheel omnidirectional drive system, running with brushless DC motors. A camera which is 3 meters above the eld provides vision feedback to identify and control the robots. Robot identification is carried out by recognizing colored patches on top of the robots. Several formation strategies are proposed using the holonomic robots we have built.
Keywords: Robotics in sports.; Robots -- Control systems.; Mobile robots.